Evaluating the treatment results of vinorelbine monotherapy in non-small cell lung cancer - Huy, Trinh Le; Loan, Nguyen Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Objective: Vinorelbine monotherapy has been shown to be effective in recurrent or metastatic nonsmall cell lung cancer. This study aimed at evaluating the treatment results of vinorelbine monotherapy in lung cancer patients relapsed after curative treatment. Patients and methods: Descriptive study of 56 non-small cell lung cancer patients who were treated with vinorelbine monotherapy relapsed after curative treatment at National Cancer Hospital between June 2018 and August 2020. Results: The mean age was 56.9 years old. Ratio male:female = 3.3:1. The percentage of adenocarcinoma and squamous cell carcinoma was 67.9% and 26.8%, respectively. Most patients (76.8%) relapsed within one year after curative treatment. The most common relapse sites were lung, bone, and pleura (85.7%, 33.9%, 30.4% respectively).The total number of treatment cycles was 428 with the average number of cycles was 6.1 ± 3.2, ranging from 2 to 21 cycles. Treatment response: no patient achieved complete response, the disease control rate was 76.8% (partial response rate 21.4%, the stable disease rate 55.4%). Histopathology and the number of relapsed site did not affect the response rate. Median PFS was 5.3 months. The number of cycles of leukopenia and neutropenia accounted for 32.5% and 34.1%, respectively, of which only 1.4% was in grade 3 and grade 4. Other common nonhematologic side effects were nausea/vomiting (15.2%); diarrhea (4.7%) and gastritis (2.8%), which were mild and did not affect the treatment course. Conclusion: Vinorelbine monotherapy is an effective option in relapsed NSCLC patients with a good safety profile. Keywords: Lung cancer, vinorelbine monotherapy, NSCLC, recurrence